ADAPTIVE ARCHITECTURE IN EXTREME ENVIRONMENTS: VERNACULAR TECHNIQUES AND SUSTAINABILITY IN AMAZONIAN RIVERSIDE COMMUNITIES - de Oliveira Junior, Jair Antonio; Meirelles, Célia Regina Moretti; Sant’Anna, Silvio Stefanini; Carbajal-Ballell, Rodrigo; de Oliveira, Silvana Rodrigues; Gobo, João Paulo Assis; Celuppi, Maria Cristina; Lima, Ana Gabriela Godinho; Fehr, Lucas; Marcondes, Flávio; Raia, Fabio; Camargo, Helena Dias de Oliveira (Seven Editora, 2026)
This article discusses the construction system of communities in floodplain regions and over water, analyzing vernacular architecture, the form of houses, their structure, enclosures, and the cultural relationship embedded in this process, especially in the Brazilian Amazon, while drawing parallels with international works. It introduces the historical issues of dwelling on and within floodplains. Therefore, it examines the relationship between riverside populations, housing, and the environment. The methods are based on a literature review and field study with site visits. The study identifies traditional stilt houses alongside floating constructions. Another relevant aspect in the Brazilian Amazon is that houses over the river accommodate not only domestic space, but also productive activities, commerce, transportation, and social practices. It is observed that riverside communities employ local materials, reuse components, and promote ecological integration, making these constructions practical examples of empirical sustainability.